Analisis Pengaruh Fear of Marriage terhadap Intensi Penundaan Pernikahan Generasi Z di Kota Semarang - Deanita Bella; Nadia Itona Siregar (Universitas Pakuan, 2026)
The development of information technology has made Generation Z in Indonesia a group highly vulnerable to exposure to digital content. In the virtual public space, the rise of the